Karakteristik, Patronage Buying Motives dan Keputusan Wisatawan Dalam Mengunjungi Desa Ekowisata Rajegwesi, Kabupaten Banyuwangi - Indra Perdana Wibisono (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract Ecotourism Rajegwesi Village in Meru Betiri National Park or Taman Nasional Meru Betiri (TNMB) has been developed as tourism destination managed incooperation with local people. However, tourist visit number still needs to be increased and the condition of tourism area is not fully satisfying the touristsexpectations. The research is descriptive and verificative, while the main data were collected through questionnaire distribution to 400 tourists who had visitedEcotourism Rajegwesi Village more than once. Based on the analysis, it is suggested that further research on the potential of travel in Betiri Meru National Park(national park). In addition TNMB suggested to business and Ecotourism Society Rajegwesi to improve the facilities in Ecotourism Rajegwesi include resting facilities(beach chair, gazebo), play facilities for the various age groups, other public facilities. Excellence attractive natural conditions need to be maintained andpreserved. Accessibility to a location that is less need to be improved in cooperation with the Department of Transportation Banyuwangi. Promotion of tourist sitesshould be increased up to national and international level to increase the number of domestic and foreign tourists visiting the country. Keyword: Ecotourism, Characteristics, Patronage Buying Motives and Purchase Decision